CITRA PEREMPUAN TOKOH NISA DALAM NOVEL ISTRI KEDUA GUS KARYA ANISA AE - Uli Wahyuni; Winda Wati (Universitas Batanghari, 2022)
This study aims to describe the female image of Nisa in the novel Istri Kedua Gus by Anisa AE. The author makes the image of women the object of this research because discussing women is always an interesting study to be researched, especially in novels. This research is included in qualitative descriptive research. This research resulted in a conclusion by not using statistical analysis tools or other quantification methods. The conclusion is in the form of a female image of Nisa in the novel Istri Kedua Gus by Anisa AE. The source of the data used is the novel Istri Kedua Gus by Anisa AE which is in the form of quotations of words, sentences, and paragraphs related to the female image of Nisa. The results showed the image of women reviewed through several aspects. These aspects are aspects of women's self-image and aspects of women's social image. Aspects of women's self-image are also reviewed through physical aspects and psychic aspects. Meanwhile, aspects of women's social image are reviewed through aspects of the image of women in the family and aspects of the image of women in society.